Global trends in geospatial conservation planning: a review of priorities and missing dimensions - Cobb, Gemma; Nalau, Johanna; Chauvenet, Alienor L. M. (Frontiers in Ecology and Evolution, 2024)
Biodiversity underpins resilient ecosystems that sustain life. Despite international conservation efforts, biodiversity is still declining due to ongoing anthropogenic threats. Protected areas have been widely adopted as a strategy for conserving biodiversity. The use of spatial conservation planning, which prioritizes areas for protection based on geo-referenced biodiversity and ecological information as well as cost of action and their feasibility, has gained popularity in the conservation discipline in the last few decades. However, there remain gaps between plans and implementation, and negative social impacts on local communities can occur, such as tension and conflict between differing priorities, perspectives, and views. To better understand the state of the spatial conservation field and support translating research into practice, a mixed-method approach of bibliometric (n=4133 documents) and content analysis (n=2456 documents) was used to analyze and identify key research priorities, collaborative networks, and geographic and thematic patterns. We identified that research conducted by westernized nations dominated the field, with the United States, the United Kingdom, and Australia being responsible for almost two-thirds of the research globally, with research interest exponentially growing since 2010. Additionally, while there has been some refinement over time of algorithms and models, Zonation and Marxan methods developed in the 2000s remain the predominant choices of software, with a majority focus on marine ecosystems, birds, and mammals. We found a major gap in the use of social dimensions in spatial conservation case studies (only n=146; 6%). This gap highlights a lack of collaboration in conservation science between researchers and local communities who are affected by management decisions. We recommend including spatially explicit social dimensions from the onset of projects through participatory approaches, along with the acknowledgement by researchers of the importance of including diverse views in conservation planning to enhance implementation and outcomes that are relevant in local contexts. We suggest an increased reflection on types of data used for conservation but also on researchers’ personal values, biases, and positionality to encourage more ethical, applicable, and collaborative conservation science.